2012
DOI: 10.1152/ajpcell.00173.2012
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide prolongs action potential duration in HL-1 mouse cardiomyocytes

Abstract: Wondergem R, Graves BM, Li C, Williams DL. Lipopolysaccharide prolongs action potential duration in HL-1 mouse cardiomyocytes. Am J Physiol Cell Physiol 303: C825-C833, 2012. First published August 15, 2012; doi:10.1152/ajpcell.00173.2012.-Sepsis has deleterious effects on cardiac function including reduced contractility. We have shown previously that lipopolysaccharides (LPS) directly affect HL-1 cardiac myocytes by inhibiting Ca 2ϩ regulation and by impairing pacemaker "funny" current, I f. We now explore fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
3
5
0
Order By: Relevance
“…Reduction in the rate of action potential rise suggested the etiology of reduced cardiac excitability was a reduction in sodium current. The in vivo data fit well with an earlier in vitro study in which application of LPS to mouse cardiomyocytes reduced excitability (785). Although the mechanism underlying the reduction in sodium current is not known, these data are consistent with an acquired sodium channelopathy in heart that affects the Na v 1.5 Na ϩ channel isoform.…”
Section: Are Electrically Active Tissues Other Than Skeletal Muscle Asupporting
confidence: 85%
“…Reduction in the rate of action potential rise suggested the etiology of reduced cardiac excitability was a reduction in sodium current. The in vivo data fit well with an earlier in vitro study in which application of LPS to mouse cardiomyocytes reduced excitability (785). Although the mechanism underlying the reduction in sodium current is not known, these data are consistent with an acquired sodium channelopathy in heart that affects the Na v 1.5 Na ϩ channel isoform.…”
Section: Are Electrically Active Tissues Other Than Skeletal Muscle Asupporting
confidence: 85%
“…We used the HL-1 cell model in this study because it displays a combination of important assets. HL-1 cells are a stable expression model, exhibit ease of transfection unlike primary cardiac myocytes, are amenable to patch-clamp and current-clamp studies, and express a complement of ion channels on the cell surface including voltage gated Na + , Ca 2+ and K + channels that resemble the ion channel types found in primary cultures of mammalian cardiac cells [ 7 , 9 , 13 , 24 , 34 , 35 ]. Nonetheless, we acknowledge that there are significant limitations related to our choice of the HL-1 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has long been attributed to the “funny current,” I f , and associated HCN channels in HL-1 cells [21] as well as well as isolated sinoatrial node cells [37]. However, our prior study of HL-1 cells [22] demonstrated I f to be activated primarily at membrane potentials more negative than the -60 to -65 mV found to be the maximal diastolic potential in the HL-1 cells [22, 23]. TRPM4 on the other hand is activated by depolarization [4] and is expressed in mouse sinoatrial node cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…About 30-40% of HL-1 cells display [Ca 2+ ] i oscillations that result in part from spontaneous action potentials, which are generated by the depolarizing I f attributed to hyperpolarization-activated cyclic nucleotide-gate (HCN) ion channels [21, 22]. We have shown that lipopolysaccharides directly inhibit HL-1 cell [Ca 2+ ] i oscillations as well as I f [22] and extend duration of the action potential [23]. We also have shown that activation of I f in HL-1 cells occurs typically at voltages more negative than the resting membrane potential of -60 mV [22].…”
Section: Introductionmentioning
confidence: 99%